Using Ipomoea aquatic as an environmental-friendly alternative to Elodea nuttallii for the aquaculture of Chinese mitten crab - Linlin Shi; Meijuan Jin; Mingxing Shen; Changying Lu; Haihou Wang; Xingwei Zhou; Lijuan Mei; Shixue Yin (PeerJ, 2019)
Elodea nuttallii is widely used in Chinese mitten crab (CMC) rearing practice, but it is not a native aquatic plant and cannot endure high temperature. Thus, large E. nuttallii mortality and water deterioration events could occur during high-temperature seasons. The aim of this study was to identify the use of local macrophytes in CMC rearing practice, including Ipomoea aquatic and Oryza sativa. A completely randomized field experiment was conducted to investigate the crab yield, water quality, bacterioplankton community and functions in the three different systems (E. nuttallii, I. aquatic, and O. sativa). Average crab yields in the different macrophyte systems did not differ significantly. The I. aquatic and O. sativa systems significantly decreased the total nitrogen and nitrate-N quantities in the outflow waters during the rearing period compared to the E. nuttallii system, and the I. aquatic and O. sativa plants assimilated more nitrogen than the E. nuttallii plant. Moreover, the significant changes of bacterioplankton abundances and biodiversity in the three systems implied that cleanliness of rearing waters was concomitantly attributed to the differential microbial community and functions. In addition, principle component analysis successfully differentiated the bacterioplankton communities of the three macrophytes systems. Environmental factor fitting and the co-occurrence network analyses indicated that pH was the driver of bacterioplankton community structure. Functional predictions using PICRUSt (v.1.1.3) software based on evolutionary modeling indicated a higher potential for microbial denitrification in the I. aquatic and O. sativa systems. Notably, the O. sativa plants stopped growing in the middle of the rearing period. Thus, the I. aquatic system rather than the O. sativa system could be a feasible and environmental-friendly alternative to the E. nuttallii system in CMC rearing practice.